It's Where You Work: Increases in Earnings Dispersion across Establishments and Individuals in the U.S. - Erling Barth; Alex Bryson; James C. Davis; Richard B. Freeman (Institute for the Study of Labor (IZA), 2014)
This paper links data on establishments and individuals to analyze the role of establishments in the increase in inequality that has become a central topic in economic analysis and policy debate. It decomposes changes in the variance of log earnings among individuals into the part due to changes in earnings among establishments and the part due to changes in earnings within-establishments and finds that much of the 1970s-2010s increase in earnings inequality results from increased dispersion of the earnings among the establishments where individuals work. It also shows that the divergence of establishment earnings occurred within and across industries and was associated with increased variance of revenues per worker. Our results direct attention to the fundamental role of establishment-level pay setting and economic adjustments in earnings inequality.
Keywords: J3; J31; D3; 330; earnings; earnings inequality; productivity